SISTEM PENGAMBIL DATA GAMBAR MENGGUNAKAN KAMERA SERIAL PADA MUATAN ROKET - Nurul Zainal Fanani; Felix V even D.C (Jurnal Teknologi Informasi dan Terapan, 2019)
KOMURINDO 2013 organized by the Directorate General of Higher Education and the Directorate of Research and Community Services together with National Institute of Aeronautics and Space gives 2 (two) theme of the competition and one of them is the High Rate Data Attitude Monitoring and Surveillance Payload. Payload or Payload Rocket is a compartment sensors telemetry data for monitoring purposes attitude and a camera for monitoring from space are arranged in a cylindrical tube measuring no more than 200mm in height and 100mm in diameter. In this final project will be discussed in accordance with the title of "Decision System Images Using Camera Serial Data on Rocket Payload" for which data will be sent to Ground Station via 433 MHz radio frequency transceiver modem YS1020U. The output of this camera series is data to hexadecimal format and not converted to images. This system can be combined with telemetry and monitoring systems for future rocket payload.